Compensation And Job Characteristics Affect Organizational Commitment With Work Environment Moderation - Fahmy, Zidni Nabila; Priyono, Bambang Suko (Universitas Pamulang, 2023)
One of the problems that often arise in internal organizations is employee work productivity, one of which is influenced by worker commitment in the organization. This study will discuss the effect of compensation, job characteristics on organizational commitment and the role of the work environment as a moderating variable. The data collection technique used by researchers is distributing questionnaires conducted online via Google form. Questionnaires filled out by respondents were subjected to instrument testing which included validity and reliability tests using the SPSS version 22.0 program, then multiple linear regression tests were performed, hypothesis testing both partially and simultaneously and Moderated Regression Analysis (MRA) tests. In accordance with the results of the discussion, there are several things that can be concluded according to the objectives of this study, namely that there is a positive influence of compensation variables, job characteristics and work environment on organizational commitment. The work environment moderates (strengthens) the effect of compensation on organizational commitment. This means that the more supportive the work environment, the stronger the relationship between compensation and organizational commitment. The work environment moderates (strengthens) the effect of job characteristics on organizational commitment.